Situation Analysis of Small-scale Mushroom Enterprises of Meghalaya in the Wake of COVID-19 Pandemic - Maring, Th Onchoila; Devarani, Loukham; Singh, R. J.; Hemochandra, L. (Indian Journal of Extension Education, 2022)
As a remunerative agri-business, mushroom farming is growing as an alternative source of income for the rural population. Meghalaya has climate highly suitable for mushroom cultivation and thus the Government of Meghalaya has taken up various interventions to popularize mushroom cultivation. The study was taken up in the East Khasi Hills and Ri-Bhoi districts of the state during 2020-2022 to analyse the situation of the mushroom enterprises in the wake of the COVID-19 pandemic, which impacted people and businesses all throughout the world. SWOT analysis and TOWS matrix were used for analysing the internal and external factors. The perceptions of 60 growers towards selected SWOT items were recorded. Important strength item was “climatic condition is congenial for mushroom” and the weaknesses was “restriction as well complexity in the mobility of the goods and persons”. For opportunities, “generates employment opportunities” had the highest score and for threats, “Unavailability of spawn” had the highest score. The study suggests establishment of mushroom based FPOs for ease of access to inputs and market for small-scale producers, the development of local spawn entrepreneurs for the accessible and timely supply of quality spawn and the creation of ICT based platform for reaching out to various backward and forward actors.
Keywords: Mushroom; COVID-19; SWOT; TOWS and Enterprises; Meghalaya